Game Theoretic Assessment of Turkey’s Role as a Transit Country amid a Changing EU’s Energy Policy - Lee, Aram; Kim, Jeonghwan (International Journal of Energy Economics and Policy, 2025)
This paper examines how changes in the gas transportation network and trade volume influence relative bargaining power. We focus on the EU as a natural gas importer and Turkey as a key transit country connecting major gas producers — Russia, Azerbaijan, and Iran. Using network game theory, we analyze the bargaining power among these participants. Our findings highlight Turkey’s critical role in the EU’s natural gas sup-ply strategy amid the Ukraine crisis. Without Turkey, access to the European gas market would be significantly restricted for other regions. While the EU’s diversification policy enhances its bargaining power, the increment remains relatively modest. Although constructing a new pipeline to bypass Turkey could strengthen the bargaining position of both the EU and gas-exporting countries, geographical and political challenges make such a project highly impractical.